Overcoming diverse approaches to vocational education and training to combat climate change: the case of low energy construction in Europe. (2nd September 2020) - Clarke, Linda; Sahin-Dikmen, Melahat; Winch, Christopher
ABSTRACT: Vocational education and training (VET) can play a transformative role in reducing CO2 emissions and improving the energy efficiency of buildings across Europe. Nearly zero energy building (NZEB) requires an energy literate workforce, with broader and deeper theoretical knowledge, higher technical and precision skills, interdisciplinary understanding, and a wide range of transversal competences. Through an investigation into VET for low energy construction (LEC) in 10 European countries, the article identifies a range of different strategies advanced under constraints imposed by the VET systems and construction labour markets. At one extreme, representing the 'high road', LEC elements are mainstreamed into broad-based occupational profiles, curricula and qualifications, whilst at the other, the 'low' road, short, specific and one-off LEC courses simply aim to plug existing 'skills' gaps. It is argued that the 'high road' approach, in encompassing a broad concept of agency, successfully addresses NZEB requirements whereas the 'low road' represents an instrumentalist approach to labour that jeopardises the achievement of higher energy efficiency standards. The article concludes by presenting a transparency tool set within the European Qualifications Framework, against which different VET for LEC programmes can be assessed.